Traders Activities In The Kertak Hanyar Sunday Market Banjar District - Rahimah Rahimah; Bambang Subiyakto; Jumriani Jumriani; M. Ridha Ilhami; Sovia Husni Rahmia (Universitas Lambung Mangkurat, 2024)
The market is a place of economic activity for the local community. Traditional markets are synonymous with the buying and selling process which is carried out through bargaining. Trader activities at the Kertak Hanyar Sunday Market occur every day and are still occurring today. However, the development of digital technology has now brought changes to society in making buying and selling easier. Of course, this threatens and disturbs the Kertak Hanyar Sunday Market traders in Banjar Regency. This article aims to describe the activities of traders at the Kertak Hanyar Sunday Market, Banjar Regency. The research method used is qualitative, and structured descriptively. The data collection techniques were carried out using observation, interviews, documentation, recording, and literature study. The results of this research describe that trader activities at the Kertak Hanyar Sunday Market are open from 08.00-16.00 WITA. Traders sell directly in the market every day, but because of the sophistication of digital technology, they are now starting to use it, such as e-commerce (electronic marketing), e-money (digital payments), and social media. Of course, this has both positive and negative impacts on traders. Therefore, there are several strategic concepts in their efforts to deal with this.